Promoting healthful family meals to prevent obesity: HOME Plus, a randomized controlled trial. Issue 1 (December 2015) - Fulkerson, Jayne; Friend, Sarah; Flattum, Colleen; Horning, Melissa; Draxten, Michelle; Neumark-Sztainer, Dianne; Gurvich, Olga; Story, Mary; Garwick, Ann; Kubik, Martha
Abstract Background Family meal frequency has been shown to be strongly associated with better dietary intake; however, associations with weight status have been mixed. Family meals-focused randomized controlled trials with weight outcomes have not been previously conducted. Therefore, this study purpose was to describe weight-related outcomes of the HOME Plus study, the first family meals-focused randomized controlled trial to prevent excess weight gain among youth. Methods Families (n  = 160 8-12-year-old children and their parents/guardians) were randomized to intervention (n  = 81) or control (n  = 79) groups. Data were collected at baseline (2011–2012), post-intervention (12-months post-baseline) and follow-up (21-months post-baseline). The intervention included ten monthly group sessions (nutrition education; hands-on meal and snack planning, preparation, and skill development; screen time reductions) and five motivational, goal-setting phone calls. The main outcome was child body mass index (BMI) z-score. Results General linear models, adjusted for baseline values and demographics, showed no significant treatment group differences in BMI z-scores at post-intervention or follow-up; however, a promising reduction in excess weight gain was observed. Post-hoc stratification by pubertal onset indicated prepubescent children in the intervention group had significantly lower BMI z-scores than their control group counterparts. Conclusions The study used a strong theoretical framework, rigorous design, quality measurement and a program with high fidelity to test a family meals-focused obesity prevention intervention. It showed a modest decrease in excess weight gain. The significant intervention effect among prepubescent children suggests the intervention may be more efficacious among relatively young children, although more research with appropriately powered samples are needed to replicate this finding. Trial registration This study is registered atwww.clinicaltrials.gov NCT01538615. Registered 01/17/2012.